Injustice impairs self-regulation and affects food choice - Macedo, V. M- C.; Correia, I.; Prada, M. (Journal of Applied Social Psychology, 2021)
Overweight and obesity are risk factors for a range of chronic diseases, many of them caused by excessive consumption of unhealthy foods and insufficient consumption of healthy foods. The present study aims to experimentally test the effect of being exposed to injustice on the intention to consume healthy and unhealthy foods, through self-regulation. We predicted that injustice decreases self-regulation which in turn increases the intention to consume unhealthy foods and decreases the intention to consume healthy foods. Undergraduate students (N = 175; 89% women; Mage = 24.28, SD = 7.36) were randomly exposed to a scenario describing an unjust or a just academic situation. In a subsequent allegedly unrelated task, participants were asked to indicate their intention to consume each of 26 food items (half depicting unhealthy foods and half healthy foods, random order) during the subsequent week. As expected, injustice decreased self-regulation which in turn increased the intention to consume unhealthy foods and decreased the intention to consume healthy foods. These results highlight the central importance of justice perceptions in the study of consumption and contribute to frame it in the study of the consequences of economic inequalities for nutrition.